I'm not a supermouse! - Stilton, Geronimo. (Geronimo Stilton., 2010)
"Yes, it's true--I'm a total 'fraidy mouse and the biggest worryrat. In fact I'm the complete opposite of my super-sporty and very brave friend Bruce Hyena. That's why I couldn't believe it when he dragged me off on a series of outrageous adventures to toughen me up. I had to keep reminding him that I'm not a supermouse! Or am I?"--P. [4] of cover.